Literary into Cultural Studies - Easthope Antony (Rouledge, 1991)
With the advent of post-structuralism and the ''death of literature'' the opposition between high and popular culture became untenable, transforming the field of inquiry from literary into cultural studies. Acknowledgements, Collapsing the Literacy Studies Paradigm, Constructing the Literary Object, Dissolving the Literary Object, The Question of Literary Value, High Culture and Popular Culture, The Canon and Its Other: Eroding the separation, High Culture and Popular Culture: Heart of Darkness and Tarzan of the Apes, Toward a New Paradigm, History and Signifying Practice, Terms for a New Paradigm, Analyzing Culture, The Subject of Literary Studies and the subject of Cultural Studies, The Politics of Cultural Studies, References, Index.